THE INFLUENCE OF MACROMEDIA FLASH LEARNING ON THE STUDENTS’ MATHEMATIC CONCEPT UNDERSTANDING - Hawa Liberna; Diah Oga Nusantari (JME (Journal of Mathematics Education), 2018)
This study aimed to determine the effect of Macromedia flash learning on the mathematical concepts understanding. This experimental research was conducted at the SMP PGRI 20 JAKARTA in the academic year 2016/2017. The sample of the research was the students of class VII with the number of students as many as 56 students consisting of 28 students of class VII-2 as the experimental group and 28 students consisting of grade VII-3 students as the control group, with different treatment from each skill program. Research data from each group was obtained by posttest using an instrument in the form of 10 items about the form of description by fulfilling the assessment aspect for the concept comprehension ability. The instruments used in this study had been tested in advance and all items were valid and had a high degree of reliability. Data analysis of research results using t-test by first testing the assumption of normality and homogeneity. The results showed that there was a significant influence of Macromedia Flash learning on the mathematical concepts understanding, especially in triangle and quadrilateral materials in class VII SMP PGRI 20 JAKARTA